2013
DOI: 10.1208/s12248-013-9514-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selected OATP and/or ABC Transporter Inhibitors on the Brain and Whole-Body Distribution of Glyburide

Abstract: Abstract. Glyburide (glibenclamide, GLB) is a widely prescribed antidiabetic with potential beneficial effects in central nervous system injury and diseases. In vitro studies show that GLB is a substrate of organic anion transporting polypeptide (OATP) and ATP-binding cassette (ABC) transporter families, which may influence GLB distribution and pharmacokinetics in vivo. In the present study, we used [11 C] GLB positron emission tomography (PET) imaging to non-invasively observe the distribution of GLB at a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 45 publications
2
57
0
1
Order By: Relevance
“…Future studies using a more physiologically relevant system, including both human liver and intestinal microsomes, may provide a better understanding on the effects of fenofibrate and gemfibrozil on the metabolism of glyburide. Interactions of glyburide with fenofibrate, gemfibrozil and simvastatin could also occur at the level of organic anion transporter polypeptides (OATPs) which have been suggested to play an important role in the pharmacokinetics of glyburide [31,32]. Glyburide is a substrate of OATP2B1 [33] and was able to inhibit OATP1B1-mediated uptake of pitavastatin in vitro [34], suggesting that it may also be a substrate of OATP1B1.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies using a more physiologically relevant system, including both human liver and intestinal microsomes, may provide a better understanding on the effects of fenofibrate and gemfibrozil on the metabolism of glyburide. Interactions of glyburide with fenofibrate, gemfibrozil and simvastatin could also occur at the level of organic anion transporter polypeptides (OATPs) which have been suggested to play an important role in the pharmacokinetics of glyburide [31,32]. Glyburide is a substrate of OATP2B1 [33] and was able to inhibit OATP1B1-mediated uptake of pitavastatin in vitro [34], suggesting that it may also be a substrate of OATP1B1.…”
Section: Discussionmentioning
confidence: 99%
“…CsA was infused for 30 min before and during the whole following PET experiment as previously described (Tournier et al, 2013).…”
Section: Pet Imagingmentioning
confidence: 99%
“…[ 11 C]dLop baseline brain distribution was found to be low and highly sensitive to P-gp (Tournier et al, 2013). Brain distribution of [ 11 C]dLop in the presence of CsA was not homogeneous and was shown to be influenced by the regional blood-flow (Liow et al, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This is especially relevant as there is a higher incidence of malaria in HIV‐infected women, and the geographic distribution of areas with high infection rates of malaria and HIV tend to overlap, resulting in significant risk of co‐infection . Next, OATP2B1 and BCRP are highly expressed in the placenta and evidence suggests that they are jointly involved in transplacental transfer of endogenous bile acids and steroid hormones as well as clinically relevant drugs such as statins and glyburide . We observed that Oatp2b1 and Bcrp were both significantly downregulated in placenta following PbA infection regardless of L‐arginine supplementation.…”
Section: Discussionmentioning
confidence: 88%